Clonal Testing of Eucalyptus Clones and Estimation of their Genetic Parameters - Kumar, Ashok; Dhillon, G. P. S. (Indian Forester, 2016)
The present study was carried out to estimate the genetic variability, heritability and genetic advance in clones of Eucalyptus spp. at Punjab Agricultural University, Ludhiana, Punjab (India). Significant differences were found among the clones for growth, number of branches and tolerance to gall wasp. The estimates of phenotypic and genotypic coefficients of variation clearly reflected large amount of variation for volume index and number of galls, and reasonable amount of genetic variability for plant height, collar diameter and number of branches. High heritability with high genetic advance as percentage of mean clearly suggested the potentiality of the clonal material for the improvement of plant height and volume index through selection. Significant positive correlations were recorded for all characters except number of galls. Path analysis revealed that plant height and collar diameter had high and positive direct and indirect effect, whereas, number of branches and number of galls had negative direct and indirect effect on volume index.